Characterization of service times and of women with breast cancer who attended in a hospital, 2005-2009 - Susan P. Martínez R; Ángela R. Segura C; Samuel A. Arias V; Gilbert. Mateus L (Universidad de Antioquia, 2012)
Objectives: to characterize the clinical and sociodemographic profiles of women with breast cancer treated at the Oncology Unit of the Federico Lleras Acosta Hospital in Ibagué, Colombia between 2005 and 2009, and to identify service times. Methodology: a retrospective descriptive study in which 308 records were selected. Variables were collected using an instrument developed by the authors. The statistical analysis was conducted using the SPSS software. Results: the predominant age group was 45 to 64 years old. Additionally, 57.8% of these women were married. Similarly, most of them were from urban areas. The average age of menarche was 13 years. Half of the participants had been pregnant at least 3 times, and most of them were in the postmenopausal stage of their lives. The most frequent histological type was the infiltrating ductal one, as well as stage IIIB. The predominant surgical choices were modified radical mastectomy, pre- and post-operative chemotherapy, and postoperative radiotherapy. As for service times, there were delays in the admission to the oncology unit and treatment initiation. Conclusion: there was a low rate of carcinoma in situ and a high proportion of stage IV carcinoma in comparison to other studies from developed countries. The high rates of abandonment in post treatment follow-up, the shortcomings in case monitoring, and the findings concerning service times suggest the need for institutional corrective measures in order to improve the quality of the healthcare service in breast cancer patients.